HEMISECTION TREATMENT AT VERTICAL ROOT FRACTURE: A CASE REPORT - Isyana Erlita (FKG Unlam, 2017)
Background: Dentistry science and technology, especially in the field of endodontics has experiencedrapid development. The advancement of dentistry has been able to keep the teeth in order to function as long aspossible in the mouth. Patient awareness to maintain current teeth is higher and prefer to be treated root canalon her teeth rather than revocation action. This is supported by the presence of advanced dental care techniquesand satisfactory results for the long term.Case: This case report aims at reporting that hemisection treatment is a treatment with considerable success.Case management: A 40-year-old female patient, coming to PPDGS RSGMP Dental Conservancy University ofAirlangga with complaints of perforated lower left molars, has often been patched but always loose and sickwhen used to chew food. Clinical features appear to be cavities in the left lower left occiput. On the objectiveexamination obtained negative vitality test, positive percussion. On the radiographic appearance radiolucencyappears to all distal roots extending to bifurcation, deep carious lesions, vertical fracture lines at distal roots.Treatment options are the hemisection and restoration of the metal fusion porcelain crown with cantilever on thelower left second mesial tooth.Conclusion: 4 weeks post-hemisection control is not found subjective or objective symptoms, it is expected thathemisection treatment with enough success rate to maintain the remaining tooth structure and functioning for aslong as possible in the oral cavity.